PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA BAGIAN KEPERAWATAN RSU MUHAMMADIYAH SURYA MELATI KEDIRI - Ika Marlianse; Eka Askafi; Supriyono Supriyono (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The purpose of this study was to determine the effect of competence and compensation on the nursing department performance at RSU Muhammadiyah Surya Melati Kediri. This study is a quantitative study that shows a causal relationship where the sample in this study was 48 nurses. Data collection techniques in this study used questionnaire, interview, and observation techniques. The analysis technique used is descriptive statistical analysis using percentages, averages and deviations standard, as well as for inferential statistical analysis using multiple linear regression tests, F test, T test, and coefficient of determination Test. The results of the study show that nurses' competencies is in good categories in terms of knowledge, skills and attitudes indicators. Compensation is also in good categories by direct compensation indicators (salary, wages, bonuses, incentives) and indirect indicators (benefits/subsidy and insurance). While the performance of the nursing department is in the good category by indicators of working quality, working quantity, working time, and cooperation. Based on multiple linear regression analysis shows that there is positive and significant effect between competence and compensation on the nursing department performance of RSU Muhammadiyah Surya Melati Kediri.